Буденна свідомість і / або повсякденність у світі релігії - Борейко, Юрій Григорович; Борейко, Юрий Григорович; Boreiko, Yurii H. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано взаємозв’язок понять «буденна свідомість» і «повсякденність» у світі релігії. Визначено компоненти буденної релігійної свідомості як носія повсякденності релігії. Найважливіша характеристика буденної свідомості – домінування смислових, ціннісних чинників над когнітивними. Значущими елементами, що кодують повсякденність релігії, є здоровий глузд, життєвий досвід, аксіологічні установки, релігійні вірування. Повсякденність забезпечує існування цих компонентів за допомогою апробації, повторення звичної, передбачуваної й одноманітної діяльності. In the article it is analyzed the interrelation of the notions «everyday consciousness» and «commonness» in the world of religion. It is defined the components of everyday religious consciousness as a medium of commonness of religion. The most important characteristics of everyday consciousness is domination of notional, valuable factors over cognitive ones. Meaningful elements that encode commonness of religion are common sense, life experience, axiological sets, and religious beliefs. Commonness ensures existence of these components by means of approbation, repeating of ordinary, foreseeable and monotonous activity. Commonness as a sphere of reality turns out to be unclosed in itself thanks to everyday consciousness that introduces into circulation new everyday structures. Everyday consciousness constantly steps outside everyday existence as it expresses not only reality of commonness, but adapts to itself spheres of uncommon activity and communication. Everything that is cognized, is created and changed in society, and is necessary for it and doesn’t step outside the limits of commonness. Studying of commonness of religion lets us synthesize the components of everyday religious consciousness (knowledge, values, etc.) and religious activity (actions, deeds, practice) of believers.
Everyday Consciousness and/or Commonness in the World of Religion
Keywords: буденна релігійна свідомість; повсякденність релігії; буття; здоровий глузд; життєвий досвід; релігійна діяльність; everyday religious consciousness; commonness of religion; existence; common sense; life experience; religious activity